2022
DOI: 10.1186/s12917-022-03339-9
|View full text |Cite
|
Sign up to set email alerts
|

Long read sequencing revealed proventricular virome of broiler chicken with transmission viral proventriculitis

Abstract: Background Transmissible viral proventriculitis (TVP) causes significant economic loss to the poultry industry. However, the exact causative agents are obscure. Here we examine the virome of proventriculus from specified pathogen free (SPF) chickens that reproduced by infection of proventricular homogenate from broiler chicken with TVP using long read sequencing of the Pacific Biosciences RSII platform. The normal SPF chickens were used as control. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Another limitation of this study is that the bacterial microbiota of other regions along the gastrointestinal tract including the main nutrient absorption sites (duodenum, jejunum, and ileum) were not examined. Finally, while the poultry gastrointestinal tract is dominated by bacteria, other microorganisms such as fungi [ 87 ], viruses [ 88 ] and archaea [ 89 , 90 ] participate in the poultry gut microbiome. Although little is known about the role of these other microorganisms in the chicken gut, elucidating the impact of dietary BSFLM as well as in-feed BMD on these microbial communities may provide insight into their performance-modulating properties.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that the bacterial microbiota of other regions along the gastrointestinal tract including the main nutrient absorption sites (duodenum, jejunum, and ileum) were not examined. Finally, while the poultry gastrointestinal tract is dominated by bacteria, other microorganisms such as fungi [ 87 ], viruses [ 88 ] and archaea [ 89 , 90 ] participate in the poultry gut microbiome. Although little is known about the role of these other microorganisms in the chicken gut, elucidating the impact of dietary BSFLM as well as in-feed BMD on these microbial communities may provide insight into their performance-modulating properties.…”
Section: Discussionmentioning
confidence: 99%
“…Gyrovirus is a single–stranded, cyclic, capsid–free virus. Studies have shown that gyrovirus can survive in low pH environments, such as gastric acid, suggesting that the virus may be highly resistant to chemical and thermal inactivation, which allows it to persist and spread in the environment [ 6 ]. Ubiquitous gyroviruses make chickens in confinement vulnerable to the virus [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The wide distribution across multiple spaces and hosts suggests a possible pathogenic hazard. In addition, the virus is highly resistant to chemical and thermal inactivation, which allows it to persist and spread in the environment [ 3 , 5 , 6 ]. Avian species have been reported to carry many gyroviruses, including the highly prevalent chicken anemia virus (CAV), a recognized pathogen of chickens worldwide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation